Effects of Tooth Brushing and MouthWashing on Leaching Bisphenol A Levels From an Orthodontic Adhesive: An In Vitro Study - Başak Arslan; Ertan Yıldırım; Onur Can Bodur; Burcu Baloş Tuncer; Mehmet Çağrı Ulusoy; Cumhur Tuncer (Galenos Yayinevi, 2022)
Objective: To assess the levels of bisphenol A (BPA) released from an orthodontic adhesive with respect to the effects of tooth brushing and mouth washing.Methods: Three groups, each containing fifteen adhesive samples were prepared. In Group 1, samples were polymerized according to manufacturer instructions. In Group 2, after the same polymerization protocol, each sample was brushed with a fluoride-containing toothpaste. For Group 3, samples were immersed in a mouth washing solution after polymerization. Later, all samples were placed into glass tubes containing 5 mL distilled water. High-performance liquid chromatography (HPLC) measurements were performed to assess the leaching amount of BPA. Intergroup comparison was performed by one way ANOVA test.Results: Mean amounts of BPA were found to be 0.2674 μg/L, 0.2692 μg/L, and 0.2705 μg/L, respectively. Only a significant difference was found between Group 1 and 3 (P < .01), revealing higher BPA levels with the mouth washing solution.Conclusion: Measurable amounts of BPA release were observed in all groups of orthodontic adhesive samples, but the detected amounts were below the toxic levels. From a clinical point of view, alcohol-containing mouth washing solutions might increase the amount of leaching monomer, since alcohol is solvent of BPA.